Effect of a neuromuscular training program on the kinetics and kinematics of jumping tasks - Chappell, J. D.; Limpisvasti, O. (The American Journal of Sports Medicine, 2008)
Altered motor control strategies are a proposed cause of the female athlete`s increased risk for noncontact anterior cruciate ligament injury. Injury prevention programs have shown promising results in decreasing the incidence of anterior cruciate ligament injury.